Do neurologists in Germany adhere to the national Parkinson's disease guideline? - Sabrina Schröder (Dove Medical Press, 2011)
Sabrina Schröder1, Daniel Kuessner2, Guy Arnold3, York Zöllner4, Eddie Jones5, Marion Schaefer11Institute of Clinical Pharmacology, Charité University Medicine, CCM, Berlin, Germany; 2Basilea Pharmaceutica, Basel, Switzerland; 3Department of Neurology, Sindelfingen-Böblingen Hospital, Sindelfingen, Germany; 4Mapi Values, Houten, The Netherlands; 5Adelphi Group Products, Macclesfield, UKAbstract: Implementation of guidelines can improve clinical practice. The aim in this study was to investigate whether neurologists in Germany adhered to the national Parkinson's disease guideline. Data were obtained from a cross-sectional survey of 60 neurologists. Analyses were performed on 320 patients with idiopathic Parkinson's disease with either low grades of functional impairment (Hoehn and Yahr stage I) or higher grades of functional impairment (stage II–V) but without motor complications. The sample was divided into four groups depending on age and grade of functional impairment. For each group, a biometric parameter on the use of dopamine agonists and L-dopa was defined based on the guideline. In patients aged <70 years, the recommendation to use dopamine agonists without L-dopa (parameter 1) was observed in 53% of patients with lower grades of functional impairment, whilst recommended use of dopamine agonists in more functionally impaired patients (parameter 2) was followed to a greater extent (84%). In patients aged ≥70 years, recommendations to use L-dopa without dopamine agonists were adhered to in only 50% of less functionally impaired (parameter 3) and 52% of more functionally impaired (parameter 4) patients. In conclusion, our results indicated there was moderate but not full adherence to the guideline.Keywords: Parkinson’s disease, dopamine agonists, L-dopa, neurologists, national guideline, Germany